Aplikasi Portal Informasi Kuliner di Surabaya Berbasis Website - Florencia, Jessica; Handojo, Andreas; -, Yulia (Jurnal Infra, 2013)
Utilization of the internet to access information via the website culinary widely applied. Various culinary website presented in a good packaged culinary information in order to culinary connoisseur can easily accesses the information. However, sometimes the lack of information on the website fail to fully support the ease of location searching.The purpose of this research about website application is to provides a place for the culinary connoisseur in accessing culinary information, particularly in Surabaya with the help of a map as a culinary signpost towards the desired spot. This application is built using the programming language PHP, Adobe Dreamweaver, and MySQL Database.From the results of the implementation and testing of a website that acts as a container of information for culinary lovers, it can be concluded that the system of culinary information retrieval has been able to function well and and got a positive response from the respondents that already testing the application.